Effect of preparation method on the oxygen vacancy concentration of CeO2-promoted Cu/gamma-Al2O3 catalysts for HTS reactions - Shim, Jae-Oh; Na, Hyun-Suk; Jha, Ajay; Jang, Won-Jun; Jeong, Dae-Woon; Nah, In Wook; Jeon, Byong-Hun; Roh, Hyun-Seog (ELSEVIER SCIENCE SA, 2016)
To investigate the effect of preparation method on the CeO2-promoted Cu/gamma-Al2O3 catalyst for the high temperature water gas shift reaction over simulated waste-derived synthesis gas, Ce/Cu/gamma-Al2O3, Ce-Cu/gamma-Al2O3, Cu/Ce/gamma-Al2O3, and Cu/gamma-Al2O3 catalysts were applied to the target reaction. Among the prepared catalysts, Ce/Cuty-Al2O3 showed the highest activity due to its high oxygen vacancy concentration and large amount of reduced Cu species, supported by XPS, Raman, and PL analysis. Additionally, TPR results showed that the catalyst preparation method effected the transformation of bulk CuO species to highly dispersed Cu-species, which influenced the catalyst activity. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: WATER-GAS SHIFT; HYDROGEN-PRODUCTION; CARBON-MONOXIDE; CO OXIDATION; X-RAY; TEMPERATURE; CERIA; PT/CEO2; OXIDE; NANOPARTICLES